An Inventory of Learning Styles Among Eleventh Graders - Garcia, Aaron Joshua N.; Castro, Clarie; Cabrera, Aryanna S.; Dayrit, Ryan; Gozun, Valerie G.; Hipolito, Kimberly; Lugtu, Ria Carla S.; Papica, Erika Dianne; Reyes, Leigh Francelle; Dominado, Noel L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to determine the learning styles of the eleventh-graders and their manifestations in terms of their learning styles. The study utilized a mixed-method research design, namely sequential explanatory design, that involved 135 respondents for the quantitative phase and eight outlier participants selected for the qualitative phase based on their higher marks from the quantitative results. The study found that among the three learning styles, namely, auditory, tactile, kinesthetic, and visual learning styles, the respondents preferred the visual learning style red among the three learning styles of the study. Also, the study findings found no significant difference between the sex of the respondents and the three learning styles. In addition, the study discovered the participants' manifestations and the utilization of various learning styles and approaches when it comes to their learning, such as studying at night, using search engines, and doing extracurricular activities to help them enhance their learning process. Finally, learning styles and strategies serve as pivotal tools for the students to be more equipped, practical, and efficient regarding their academic performance at school. Hence, students, teachers, and school administrators should be able to understand various learning styles and approaches. Also, future researchers should study the environmental factors that affect students' learning process.